Maksimovka I Grave Field (Forest-Steppe Volga Region): Results of the 2019 Excavations - Arkadii I. Korolev; Anton A. Shalapinin (Oriental Studies)
Introduction. The work publishes some results of excavations at the Maksimovka I grave field. Goals. So, the article seeks to introduce materials of the 2019 excavations. To facilitate this, the paper shall describe and characterize the investigated archaeological complexes, establish their cultural and chronological attributions. Materials. Archaeological material from the occupation layer comprises Neolithic, Chalcolithic, Bronze Age, and eighteenth/twentieth century pottery, flint tools, and stone processing waste. Six burials were investigated at the site. Two burials had been destroyed and are nothing but heaps of heavily fragmented bones with no grave goods observed. In the third burial, the skeleton was lying on back in a northern-northwestern direction, accompanied by an iron knife and goat/sheep bones. The next burial consisted of four skulls and compact clusters of skeletal bones located nearby. The latter’s grave goods included flint arrowheads, a scraper, a bone spearhead, a pendant, beads, piercings and marmot incisors. The fifth burial contained a seated skeleton facing northeast and accompanied by a flint plate, an arrowhead and beads. In the last burial, the skeleton was lying on back in a northern-northwestern direction, accompanied by an ornamented clay vessel. A part of structure 1 was also examined. Results. The work shows that a total of three burials date back to the Late Chalcolithic, one — to the Late Bronze Age, and one — to the Middle Ages. The cultural and chronological attribution of the remaining burial has not been determined yet. Conclusions. The excavations at the Maksimovka I grave field have yielded materials from different cultures and periods, including Neolithic, Chalcolithic, Bronze Age, and Medieval complexes.